2019
DOI: 10.1111/jam.14233
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the denitrification pathway and greenhouse gases emissions inBradyrhizobiumsp. strains used as biofertilizers in South America

Abstract: Aims: Greenhouse gases are considered as potential atmospheric pollutants, with agriculture being one of the main emission sources. The practice of inoculating soybean seeds with Bradyrhizobium sp. might contribute to nitrous oxide (N 2 O) emissions. We analysed this capacity in five of the most used strains of Bradyrhizobium sp. in South America. Methods and Results: We analysed the denitrification pathway and N 2 O production by Bradyrhizobium japonicum E109 and CPAC15, Bradyrhizobium diazoefficiens CPAC7 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…On the contrary, inoculants based on nosZ − B. japonicum such as USDA138 would not be able to do so. This fact was also reported for soybean inoculation in South America [11,32], where the inoculant strains used are nosZ − and are unable to reduce N 2 O. Nevertheless, in situations with natural nodulating populations, more investigations are required on the competitiveness of selected strains in order to obtain a successful inoculation (i.e., the inoculant strain occupying a significant proportion of nodules formed on the roots).…”
Section: Discussionsupporting
confidence: 55%
“…On the contrary, inoculants based on nosZ − B. japonicum such as USDA138 would not be able to do so. This fact was also reported for soybean inoculation in South America [11,32], where the inoculant strains used are nosZ − and are unable to reduce N 2 O. Nevertheless, in situations with natural nodulating populations, more investigations are required on the competitiveness of selected strains in order to obtain a successful inoculation (i.e., the inoculant strain occupying a significant proportion of nodules formed on the roots).…”
Section: Discussionsupporting
confidence: 55%
“…Bradyrhizobium inoculants are alternatives to reduce water pollution and nitrous oxide (N 2 O) emission (Akiyama et al, 2016). However, Obando et al (2019) showed the first report that pointed out the incomplete denitrification pathway in five of the most used strains for soybean. Göttfert et al (2001) described symbiosis-specific genes in a 410-kilobase DNA region of the B. diazoefficiens USDA110 chromosome and in 2002, the complete genomic sequence was described (Kaneko et al, 2002).…”
Section: Bradyrhizobium Species In Brazilian Soilsmentioning
confidence: 99%
“…The greenhouse gas N 2 O is produced during nitrification and denitrification ( 1 4 ). The N 2 O reductase encoded by the nosZ gene is the only enzyme that can reduce N 2 O to the nongreenhouse gas N 2 ( 5 8 ). In this study, bioinformatic tools were used for genome assembly and annotation of nosZ gene-containing bacterial genomes recovered from the metagenomic data for samples enriched with N 2 O.…”
Section: Announcementmentioning
confidence: 99%